2021
DOI: 10.1016/j.resinv.2021.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography at every step: Long coronavirus disease

Abstract: Background Some patients continue to experience symptoms related to Coronavirus disease (COVID-19) after the acute phase of infection. Imaging studies, especially computed tomography (CT) of the chest, have gained importance since the beginning of the pandemic. CT can help diagnose COVID-19, assess the extent of pulmonary involvement, and predict the disease severity. We aimed to define the frequency of persistent symptoms and correlate their presence with the results of laboratory findings and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Regarding underlying mechanisms, several papers reported that post-COVID breathlessness was correlated with reduced spirometry parameters (n=5) [ 32 , 42 , 58 60 ], lower diffusion capacity for carbon monoxide ( D LCO ) (n=7) [ 32 , 36 , 55 , 58 , 59 , 61 , 62 ] and lung imaging abnormalities (computed tomography (CT) (n=3) [ 40 , 58 , 63 ], lung ultrasound (n=1) [ 36 ], chest radiograph (n=1) [ 42 ]), but four [ 26 , 37 , 55 , 61 ], four [ 26 , 37 , 60 , 64 ] and three papers [ 35 , 37 , 65 ] found no significant associations with these three measurements, respectively. One paper [ 26 ] reported that patients with post-COVID breathlessness had reduced exercise capacity based on the 6-minute walk test, lower predicted peak oxygen consumption and worse performance in cardiopulmonary exercise testing; another paper [ 59 ] also found a reduced 6-minute walk distance and lower end-exercise oxygen saturation, and two additional papers [ 38 , 66 ] supported the findings in cardiopulmonary exercise testing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding underlying mechanisms, several papers reported that post-COVID breathlessness was correlated with reduced spirometry parameters (n=5) [ 32 , 42 , 58 60 ], lower diffusion capacity for carbon monoxide ( D LCO ) (n=7) [ 32 , 36 , 55 , 58 , 59 , 61 , 62 ] and lung imaging abnormalities (computed tomography (CT) (n=3) [ 40 , 58 , 63 ], lung ultrasound (n=1) [ 36 ], chest radiograph (n=1) [ 42 ]), but four [ 26 , 37 , 55 , 61 ], four [ 26 , 37 , 60 , 64 ] and three papers [ 35 , 37 , 65 ] found no significant associations with these three measurements, respectively. One paper [ 26 ] reported that patients with post-COVID breathlessness had reduced exercise capacity based on the 6-minute walk test, lower predicted peak oxygen consumption and worse performance in cardiopulmonary exercise testing; another paper [ 59 ] also found a reduced 6-minute walk distance and lower end-exercise oxygen saturation, and two additional papers [ 38 , 66 ] supported the findings in cardiopulmonary exercise testing.…”
Section: Resultsmentioning
confidence: 99%
“…Four papers [ 26 , 32 , 61 , 66 ] assessed echocardiogram results during follow-up but only one [ 66 ] detected an association with post-COVID breathlessness. One paper [ 63 ] identified a correlation with higher C-reactive protein (CRP) level at the follow-up visit, but another paper [ 42 ] did not. Three papers [ 32 , 35 , 48 ] reported significant associations between post-COVID breathlessness and symptoms of depression and anxiety, one of which also reported an association with post-traumatic stress disorder [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thorax computed tomographic (CT) findings have been reported to be useful for the diagnosis, prognostic assessment, and detection of complications of COVID-19 infection [ 4 ]. CT severity score assessed based on the percentage of lung involvement has been shown to be a good prognostic predictor in patients with COVID-19 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%